NYĀYA THEORY OF IMPLICATION AND INTERPRETATION - Vattanky, John (Journal of Dharma, 2005)
It is well known that in contemporary Western philosophy, especially under the influence of Gadamer, Ricoeur, and so on, hermeneutics and allied disciplines are assuming more and more significance. The influence of these hermeneutical theories has gradually been felt also on present day Indian thought. What, however, is not so well known even among Indian philosophers themselves is that India had a long and distinguished history of theories of interpretation. Mimāmsa system, for example, tried to lay down the rules of interpretation in order to arrive at the true meaning of the Vedas. The discipline of Grammar, which again had a long history in India, reached its philosophical heights in the path-breaking works of Bharthari. Philosophers of Grammar had to struggle with the problem of meaning and in some ways also with the question of interpretation. In the Nyāya system, discussions on the philosophy of language and theories of interpretation were carried on largely in the context of the discussions on śabda (word), as a means of valid verbal knowledge. There is no treatise exclusively on interpretation as such in the modern sense. Yet, on the basis of what the Naiyāyikas have contributed towards a philosophy of language, we can construct a theory of interpretation adequate to meet the philosophical challenges of today. The present essay is an attempt to develop such a theory of interpretation based on the Nyāya contribution on the philosophy of language in general and implication in particular.